2006
DOI: 10.1007/s10711-006-9109-5
|View full text |Cite
|
Sign up to set email alerts
|

On the convergence of metric and geometric properties of polyhedral surfaces

Abstract: We provide conditions for convergence of polyhedral surfaces and their discrete geometric properties to smooth surfaces embedded in Euclidean 3-space. Under the assumption of convergence of surfaces in Hausdorff distance, we show that convergence of the following properties are equivalent: surface normals, surface area, metric tensors, and Laplace-Beltrami operators. Additionally, we derive convergence of minimizing geodesics, mean curvature vectors, and solutions to the Dirichlet problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
140
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(142 citation statements)
references
References 35 publications
1
140
0
1
Order By: Relevance
“…Hildebrandt et.al's work [23] focuses on the equivalence of convergence of polyhedral meshes under different metrics, such as Hausdorff, normal, area and Laplace-Beltrami. Assuming the Hausdorff convergence and the homeomorphism between the surface and the mesh, all the error estimations are based on the homeomorphism.…”
Section: Comparisons To Previous Theoretical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hildebrandt et.al's work [23] focuses on the equivalence of convergence of polyhedral meshes under different metrics, such as Hausdorff, normal, area and Laplace-Beltrami. Assuming the Hausdorff convergence and the homeomorphism between the surface and the mesh, all the error estimations are based on the homeomorphism.…”
Section: Comparisons To Previous Theoretical Resultsmentioning
confidence: 99%
“…These important applications demand the theoretical guarantee for accurate approximation for Riemannian metric and differential operators. It has been shown in [23], Hausdorff convergence and normal field convergence guarantee the convergence of area, Riemannian metric tensor and Laplace-Beltrami operator.…”
Section: Geometric Accuracymentioning
confidence: 97%
“…[23,24] Φ(e) is the signed dihedral angle between the faces, f 1 (e) and f 2 (e), taking a value of π when the faces are coplanar . R(e) is the length of the edge.…”
Section: In-plane Orientational Ordermentioning
confidence: 99%
“…For example, Meyer et al (2002) proposed a cotangent formula for estimating mean curvatures, which is closely related to the formula for Dirichlet energy of Pinkall and Polthier (1993). It was shown that the cotangent formula does not produce converging pointwise mean-curvature estimations except for some special cases, as noted in Borrelli et al (2003), Xu (2004), Hildebrandt et al (2006), Wardetzky (2007). As another example, Langer et al (2007) proposed a tangent-weighted formula for estimating mean-curvature vectors, whose convergence relies on special symmetric patterns of a mesh.…”
Section: Introductionmentioning
confidence: 99%